A quantitative method for evaluating GNSS signal disruption in sports stadiums - Kim, M.; Mills, K. L.; Kim, B.; Park, C.; Yoon, J.; Parkinson, T.; Billingham, J. (Sports Engineering, 2025)
This study introduces a quantitative method to evaluate the impact of roof coverage in football stadiums on GNSS (Global Navigation Satellite System) signal quality. GNSS is often used to track the positions of players in outdoor sports. However, stadium roofs or other structural obstacles can degrade the GNSS signal quality, and reduce the overall quality of the data. Given that many players compete across a variety of venues, each with different structural characteristics, this study investigated and analyzed the relationship between the stadium environment and GNSS signal performance. A methodology was developed to quantify the impact of roof coverage on GNSS signal quality. This was followed by hardware experiments that used the proposed method. A strong positive correlation (r = 0.98, p < 0.01) was found between the GNSS performance attenuation ratio and the GNSS positioning error standard deviation. The results can help coaches and analysts improve the accuracy of player performance evaluations based on positional data in stadium environments.